EFFECT OF NPK FERTILIZER AND AGROLYSER ON GROWTH, YIELD AND YIELD COMPONENTS OF MAIZE IN NORTHEASTERN NIGERIA - IBRAHIM, A. K; AHMED, U; GIREI, A. H (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2022)
A field experiment was conducted at the Teaching and Research Farm of the Federal University of Kashere in the 2018 and 2019 cropping seasons to evaluate the effectiveness of sole and combined application of NPK fertilizer and agrolyser (micronutrient) on the growth and yield of maize. The experiment was factorial and laid out in Randomized Complete Block Design with three replications, comprising 9 treatments. The treatments were three levels each of NPK fertilizer (0, 100 and 150 kg ha-1 NPK fertilizer) and agrolyser (0, 3 and 5 kg ha-1). The results indicated that the combined application of NPK and agrolyser significantly increased (p< 0.05) plant height (129.8 to 64 cm) and grain yield (1534.4 to 2315.2 kg/ha) in the 2018 and 2019 seasons respectively. Application of NPK at the rate of 150 kg ha-1 increased the plant height (139 to 189 cm) and grain yield (1773 to 2619 kg/ha) in the 2018 and 2019 cropping seasons respectively. Application of agrolyser at the rate of 3 kg ha-1 increased all the studied characters, but a further increase in rate from 3 to 5 kg ha-1 did not significantly increase the studied parameters any further. A combination of NPK (150 kg ha-1) and agrolyser (3 kg ha-1) recorded the highest mean values of plant height (183.7 cm), the number of cobs (47.6), 100-grain weight (23.1 kg/ha) and grains yield (2353 kg/ha) in both harvest years. It was, therefore, concluded that combined application of NPK fertilizer and agrolyser at the rates of 150 and 3 kg ha-1 respectively are the most suitable rates for maximum grain yield of maize